PENGARUH SUPLEMENTASI FERMENTASI DAUN KELOR TERHADAP KONSUMSI BK DAN METABOLIT DARAH DOMBA LOKAL JANTAN - Aliyah, Hasna Nisa Salma; Purwadi, Purwadi; Suhardi, Suhardi (Tropical Animal Science, 2023)
The purpose of this study was to determine the effect of moringa fermentation supplementation in the diet on the blood metabolites of local male sheep on the consumption of BK and blood metabolites. This research was conducted from May to June 2021 at the sheep farm owned by Bp. Miranto is located in Sedayu Village, Tulung District, Klaten Regency. The material used was 14 male local sheep aged 1 year with an average weight of 18.69 kg. The equipment used is a scale, stationery, cleaning equipment, syringe, cotton, ice flask, ice cubes, and alcohol. This study used a completely randomized design (RAL) with 2 treatments and 6 replications. The treatments were T0 = Moringa leaf fermented supplement 0% + 40% concentrate + 60% elephant grass, T1 = Moringa fermentation supplement 25% + 25% concentrate + 50% elephant grass. The results of the study were analyzed using the ANNOVA test, the results of this study were that the administration of moringa fermented supplementation as much as 25% had a significant effect on BK consumption, namely reducing BK consumption but did not affect blood glucose levels, blood protein levels, blood urea levels, blood albumin levels, and blood glucose levels. blood triglycerides. This shows that Moringa fermentation provides higher nutrient quality, as seen with lower BK consumption producing the same blood metabolites in male local sheep. Keywords: Sheep, feed, Moringa leaves, fermentation, blood metabolites, BK consumption.